Dogs perceive and spontaneously normalize formant-related speaker and vowel differences in human speech sounds. (4th December 2019) - Root-Gutteridge, Holly; Ratcliffe, Victoria F.; Korzeniowska, Anna T.; Reby, David
Abstract : Domesticated animals have been shown to recognize basic phonemic information from human speech sounds and to recognize familiar speakers from their voices. However, whether animals can spontaneously identify words across unfamiliar speakers (speaker normalization) or spontaneously discriminate between unfamiliar speakers across words remains to be investigated. Here, we assessed these abilities in domestic dogs using the habituation–dishabituation paradigm. We found that while dogs habituated to the presentation of a series of different short words from the same unfamiliar speaker, they significantly dishabituated to the presentation of a novel word from a new speaker of the same gender. This suggests that dogs spontaneously categorized the initial speaker across different words. Conversely, dogs who habituated to the same short word produced by different speakers of the same gender significantly dishabituated to a novel word, suggesting that they had spontaneously categorized the word across different speakers. Our results indicate that the ability to spontaneously recognize both the same phonemes across different speakers, and cues to identity across speech utterances from unfamiliar speakers, is present in domestic dogs and thus not a uniquely human trait.